Shock in pediatric infection diseases - B. M. Blokhin; I. V. Gavryutina (LLC "Diagnostics and Vaccines", 2019)
Shock is a frequent, lethally dangerous complication of infectious diseases in children. The main reason for high mortality among children population is late diagnostics and irrational therapy. The variability of clinical picture urges to develop a clear algorithm for searching shock markers and therapeutic approaches depending on the severity.